2007
DOI: 10.1109/led.2006.887941
|View full text |Cite
|
Sign up to set email alerts
|

Effect of $\hbox{F}_{2}$ Postmetallization Annealing on the Electrical and Reliability Characteristics of HfSiO Gate Dielectric

Abstract: The effects of fluorine (F 2 ) annealing on the electrical and reliability characteristics of HfSiO MOSFETs were investigated. Compared with a control sample annealed in conventional forming gas (H 2 /N 2 = 4%/ 96%), additional annealing in a fluorine ambient (F 2 /Ar = 0.3%/ 99.7%) at 400 • C for 20 min improved the electrical characteristics such as lower interface trap density and higher transconductance. In addition, MOSFET samples annealed in a F 2 ambient exhibited less degradation under hot-carrier stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…[15][16][17][18] The reduction of D it for the pre-F is attributed to the effective passivation of Si dangling bonds resulting from Si-F bonding formation. 7 The positive shift of V FB is due to the negative fixed charge induced by incorporated F atoms, in agreement with a previous report. 19 However, we cannot exclude the possibility that D it also contributes to V FB shift.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…[15][16][17][18] The reduction of D it for the pre-F is attributed to the effective passivation of Si dangling bonds resulting from Si-F bonding formation. 7 The positive shift of V FB is due to the negative fixed charge induced by incorporated F atoms, in agreement with a previous report. 19 However, we cannot exclude the possibility that D it also contributes to V FB shift.…”
Section: Resultssupporting
confidence: 92%
“…F atom implantation was used in an early study, but implanting F was shown to cause uncontrolled oxide regrowth during the gate-stack process. 6 As an alternative, high-temperature F 2 annealing or UV-assisted F 2 annealing was reported to result in effective incorporation of F. 3,7 More recently, F treatment using highly reactive radicals from CF 4 plasmas was reported on the HfO 2 gate oxide prepared by sputtering. 4,8,9 This method is especially preferable for the F treatment of high-k films prepared by a deposition technique using plasma such as plasma-enhanced atomic layer deposition ͑PE-ALD͒, because F treatment can be carried out in situ inside of the deposition chamber.…”
mentioning
confidence: 99%
“…On the contrary, the F concentrations at the interfaces show a significant increase after the additional annealing process with annealing temperature and time. Si-F bonds are stronger and more difficult to break under stress than Si-H and Si-Cl bonds [21][22][23]; thus, we chose an additional FGA process at 450 °C for 60 min as our optimized annealing condition for fabricating the annealingoptimized p-FinFETs, as shown in Fig. 1a.…”
Section: Resultsmentioning
confidence: 99%
“…Several fluorine passivation technologies have been mentioned to improve device reliabilities, such as tetrafluoromethane ͑CF 4 ͒ plasma treatment, 8 channel fluorine implantation, 9 source/drain region fluorine implantation, 10 and F 2 gas anneal. 11 In this letter, a fluorination process using fluorinated silicate glass ͑FSG͒ passivation layer has been introduced. The electrical characteristics and dielectric reliabilities of n-channel metal-oxide-semiconductor fieldeffect-transistors ͑nMOSFETs͒ with the FSG fluorinated HfO 2 / SiON gate dielectric has been investigated comprehensively.…”
Section: Improved Performance and Reliability For Metal-oxide-semiconmentioning
confidence: 99%